The Influence of Task Characteristics and Technology Functionality on Task-Technology Fit and Service Level Performance in Fulfillment Centers: Evidence from a Startup Context - Ramadani, Dani (Universitas Nahdlatul Ulama Surabaya, 2025)
Fulfillment Center is a special facility designed to manage order processing and product fulfillment for e-commerce businesses. The fulfillment center has a service level agreement (SLA) that must be met as a form of prime performance. Analysis of the determinants of Service Level Performance in Fulfillment Centers is conducted within the framework of Task Technology Fit. This study aims to analyze the effect of Characteristics and Technology Functionality on Service Level Performance in Fulfillment Centers with task technology fit as a mediating variable. This study is a quantitative study of 100 employees in the picking and packing division using a questionnaire. The analysis method used is SEM-PLS. The results of the analysis show that Task Characteristics have a positive and significant effect on Task Technology Fit. Technology Functionality has a positive and significant effect on Task Technology Fit. Task Technology Fit mediates the effect of Task Characteristics on the Fulfillment Center Service Level and is proven to be statistically significant. Task Technology Fit mediates the effect of Task Characteristics on the Fulfillment Center Service Level and is proven to be statistically significant.